An Empirical Study on the Progression of Self Help Groups in India - Saranya C; K. Sita Devi (Archives of Current Research International, 2024)
As per NABARD report, India has the largest microfinance programme in the world with 17.80 crores of household through more than 144 lakh SHGs with deposit of Rs. 65, 089 crores, Rs. 2,09,286 crores as annual loan offtake and Rs. 2, 59, 664 crores as outstanding loan with an average of Rs. 3.35 lakh per SHG. With this background, this present study has been carried to study the performance of SHGs for the period from 2009-10 to 2023-24. The compound annual growth rate has revealed that the overall growth of loan amount availed by SHGs (19.93 per cent) has the greatest growth rate, when compared to saving amount and outstanding amount. The Cuddy Delle Valle Instability index has revealed that the saving amount and outstanding loan against SHGs has low instability. This shows that the SHG-BLP is progressing among the rural people through National Rural Livelihoods Mission and National Urban Livelihoods Mission. The financial literacy and capacity building has been increasing by means of mobilisation of money.